Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1468-3083.2010.03603.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of ulcerated haemangioma with propranolol

Abstract: Propranolol may be the first-choice therapy for ulcerated haemangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…Recently, a few case series of patients with ulcerating IH successfully treated with propranolol have been described. [8][9][10] As a great number of patients with complicated IH are treated at our tertiary referral center, it was possible to select a similar control patient from our historical database for each of the propranololtreated cases. After the two groups were compared, it was found that the mean ulceration time was significantly shorter for the patients treated with propranolol compared with the historical matched control group (8.7 vs 22.4 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few case series of patients with ulcerating IH successfully treated with propranolol have been described. [8][9][10] As a great number of patients with complicated IH are treated at our tertiary referral center, it was possible to select a similar control patient from our historical database for each of the propranololtreated cases. After the two groups were compared, it was found that the mean ulceration time was significantly shorter for the patients treated with propranolol compared with the historical matched control group (8.7 vs 22.4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…8 There have been several case-reports of propranolol therapy for ulcerating IH, but no comparative studies have been published. [8][9][10] In our study, the role of this nonselective beta-blocker was explored by treating 20 patients with an ulcerating IH in the proliferation phase and comparing this patient group with similar historical controls.…”
Section: Introductionmentioning
confidence: 99%
“…25 Previous reports of propranolol treatment of IH did not comment on or reported limited sideeffects. [5][6][7][8][9][10][11][12][13] A possible explanation for this difference may be our multidisciplinary approach in which patients are frequently evaluated and closely monitored in the outpatient clinic by a pediatrician, a pediatric dermatologist, and/or a pediatric plastic surgeon. However, information from a case series has limitations and further clinical studies are necessary to determine the incidence of these adverse effects.…”
Section: Side Effectsmentioning
confidence: 99%
“…4 Recently, Léauté-Labrèze et al 5 reported a spectacular response to treatment of IH with propranolol, and this was confirmed in other studies. [6][7][8][9][10][11][12][13] We describe the results of propranolol treatment and associated side effects in 28 patients with IH.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hemangiomas are active proliferating tumors which demonstrate a characteristic pattern of rapid postnatal growth followed by slow involution [2,3]. Although the serendipitous discovery of the therapeutic efficacy of propranolol in the management of infantile hemangiomas has revolutionized the care and outcomes of these lesions [5,6], there is no standard treatment protocol for the management of VM. Treatment options of low flow VM include simple observation, minimally invasive interventions such as sclerotherapy or embolization [7,8], laser ablation [9], cryotherapy [10], or more aggressive surgical resection.…”
Section: Introductionmentioning
confidence: 99%